Local suppression of T cell responses by arginase-induced L-arginine depletion in nonhealing leishmaniasis. - Manuel Modolell; Beak-San Choi; Robert O Ryan; Maggie Hancock; Richard G Titus; Tamrat Abebe; Asrat Hailu; Ingrid Müller; Matthew E Rogers; Charles R M Bangham; Markus Munder; Pascale Kropf (Public Library of Science (PLoS), 2009)
The balance between T helper (Th) 1 and Th2 cell responses is a major determinant of the outcome of experimental leishmaniasis, but polarized Th1 or Th2 responses are not sufficient to account for healing or nonhealing. Here we show that high arginase activity, a hallmark of nonhealing disease, is primarily expressed locally at the site of pathology. The high arginase activity causes local depletion of L-arginine, which impairs the capacity of T cells in the lesion to proliferate and to produce interferon-gamma, while T cells in the local draining lymph nodes respond normally. Healing, induced by chemotherapy, resulted in control of arginase activity and reversal of local immunosuppression. Moreover, competitive inhibition of arginase as well as supplementation with L-arginine restored T cell effector functions and reduced pathology and parasite growth at the site of lesions. These results demonstrate that in nonhealing leishmaniasis, arginase-induced L-arginine depletion results in impaired T cell responses. Our results identify a novel mechanism in leishmaniasis that contributes to the failure to heal persistent lesions and suggest new approaches to therapy.